COURSERA ONLINE COURSE: A PLATFORM FOR ENGLISH TEACHERS' MEANINGFUL AND VIBRANT PROFESSIONAL DEVELOPMENT - Silvia, Arnis (TEFLIN Journal, 2015)
This article reports on English teachers‘ attitudes towards a professional development program run by Coursera (coursera.org). These teachers were participants of Foundation of Teaching for Learning 1: Introduction online course. Using a survey case study, the findings reveal that most of the participants perceive the course as a well-organized and effective platform to engage in professional learning. Coursera is an online learning platform offering various courses for teacher educators which are meaningful (closely related to their daily teaching practice) and vibrant (involves active collaboration among peer participants to review and assess their projects). Albeit this nature, another finding shows that the participants lament that their institutions do not provide professional development (PD) support. In fact, PD programs are not constrained to face-to-face encounters, since it can be designed using online platforms such as Coursera, a massive open online course (MOOC). Accordingly, the contribution of the article is to show how online platforms make meaningful and vibrant teacher professional development (TPD) possible. The implication of the study is that school administrators and policy makers should provide support for their teachers to take online PD programs. This professional learning should contribute to the best teaching practice and student learning attainment.